Glassy carbon electrodes modified with a dispersion of multi-wall carbon nanotubes in dopamine-functionalized polyethylenimine: Characterization and analytical applications for nicotinamide adenine dinucleotide quantification - Gasnier, Aurelien (2012)
We report the characterization of a dispersion of multi-wall carbon nanotubes (CNT) in a solution of polyethylenimine (PEI) functionalized with dopamine (Do), the electrochemical behavior of glassy carbon electrodes (GCE) modified with the resulting dispersion, and its analytical application for the highly sensitive quantification of NADH without fouling of the surface. The dispersion was obtained by sonicating for 60 min 1.0 mg CNT in 1.0 mL of 1.0 mg/mL PEI-Do solution prepared in 50/50 (v/v) ethanol/water. The presence of Do covalently bonded to PEI promotes hydrophobic π interactions with the CNT walls and improves significantly the dispersability of CNT in this mixture. The dispersion is highly stable since after 2 months resting at room temperature no phase separation was observed. This dispersion was dropcoated over GCE, and after solvent evaporation, a very reproducible and uniform coverage was obtained. An electrochemical pretreatment (activation) of such a modified GCE electrode allowed the sensitive quantification of NADH at potentials as low as -0.025 V. The response of NADH at the electrochemically activated GCE modified with the dispersion of CNT in PEI-Do solution (GCE/CNT-PEI-Do), demonstrated to be highly reproducible. The R.S.D. for the NADH sensitivity obtained with 15 electrodes and 3 different dispersions was 8.9%. Even more important, after 10 calibrations for NADH with the same surface the decrease in the sensitivity was smaller than 10%. The dispersion was characterized by Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared Spectroscopy (FT-IR) while the electrodes modified with the dispersion were evaluated using different electrochemical techniques (Cyclic voltammetry (CV), Amperometry and Electrochemical Impedance Spectroscopy (EIS)). © 2012 Elsevier Ltd. All rights reserved.